2012
DOI: 10.1111/j.1753-9137.2012.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Text-Visual Frames of Sub-Saharan Africa in the News: A Comparison of Online News Reports From Al Jazeera and British Broadcasting Corporation Websites

Abstract: This study presents a comparative analysis of 311 online news stories collected for 3 months from Al Jazeera and British Broadcasting Corporation (BBC) African news front pages with respect to both their text–visual valence and the overall portrayal of sub‐Saharan Africa. Results showed that text–visual complementarities in news reporting were primarily consonant, though a considerable portion of news reporting was dissonant implying that what is textually presented can differ in tone from what is visually sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…while visual frames work in tandem with textual frames to create an overarching news frame (Mellese & Müller, 2012), this study demonstrates how independent and powerful visuals are in framing dissenting voices in the public sphere. The article analyzed a total of N=852 images published in Canadian mainstream media, including eight newspapers and the websites of two leading national news broadcasters.…”
Section: Discussionmentioning
confidence: 80%
“…while visual frames work in tandem with textual frames to create an overarching news frame (Mellese & Müller, 2012), this study demonstrates how independent and powerful visuals are in framing dissenting voices in the public sphere. The article analyzed a total of N=852 images published in Canadian mainstream media, including eight newspapers and the websites of two leading national news broadcasters.…”
Section: Discussionmentioning
confidence: 80%
“…The literature on mediated imagery of Africa is extensive and notably convergent on a number of topics. 3 Previous research has suggested that Africa’s presence in the media tends to be scarce when compared to other world regions (Kalyango Jr. and Onyebadi, 2012; Terrell, 1989; Wilke et al, 2012), narrow in the topics covered and frames used (de Beer, 2010; Fair, 1993; Hawk, 1992; Mellese and Müller, 2012), predominantly negative (El Zein and Cooper, 1992; Golan, 2008; Schraeder and Endless, 1998) and, as just mentioned, dominated by ‘Western’ perspectives (Malaolu, 2014; Paterson, 1994). These characteristics have been identified across media, in both news and entertainment, and across genres.…”
Section: Representations Of Africa In the Mediamentioning
confidence: 99%
“…Limited studies have used CDA and MDA to research online news discourse. Whilst Knox (2007) attempted to compare visual-verbal structures between print and online news, Mellese and Muller (2012) as well as Wessler, Wozniak, Hofer, and Luck (2016) conducted comparative analyses of multimodal news frames via the comparison of text-visual frames of distinct online newspapers. Analyzing news stories on official websites of online newspapers, barely did the aforementioned studies take into consideration novel online platforms available for news broadcasting.…”
Section: Literature Reviewmentioning
confidence: 99%